HEISQUAL – ACSI – IPA – PGCV: Synthesis of higher education service satisfaction measurements - Raharjo, Teguh Hardi; Mulyono, Kemal Budi; Ismiyati, Ismiyati; Jaenudin, Ahmad (Asian Management and Business Review, 2023)
The current weakness of various dimensions of service quality measurement scales that have been adopted in measuring the level of student service satisfaction at HE is often an obstacle to understanding weaknesses in the quality of HE service. This study aims to investigate the level of student service satisfaction based on the HEISQUAL synthesis combined with the ACSI, IPA, and PGCV methods as a holistic approach to determine priorities for continuous improvement. The integration of these three methods is very appropriate to answer the needs of HE in improving the quality of its services. The data in this study were obtained by distributing questionnaires to respondents with a sample size of 320 students using a convenience sampling technique (non-probability sampling). The results of this study indicate that HE service satisfaction is in the satisfied criteria, where 6 sub-dimensions are in quadrant A, 5 sub-dimensions are in quadrant B, 1 sub-dimension is in quadrant C, and 4 sub-dimensions are in quadrant D. From this analysis, the priority order of improvement are 1) ET, 2) LWE, 3) LF, 4) ECA, 5) C&M, 6) BTS. Through the HEISQUAL – ACSI – IPA – PGCV synthesis, HE can understand and determine well-accelerated strategic and practical policies.